Efeito magneto-óptico em mistura binária dopada com ferrofluido - Laczkowski, Ivan Marcelo (2010)
In this work, we investigate the magneto-optical effect in a binary mixture of water and glycerin doped with ferrofluid, emphasizing its relationship with the static and relaxation processes. We discuss the main features of magnetic fluids, the synthesis of these materials by the method of chemical co-precipitation, the optical transmittance and a data acquisition system which was developed to enable the relaxation measurements and other measurements of transmittance. We have also studied the behavior of the viscosity of our samples as a function of temperature, and by using the static magnetic birefringence technique, we describe the optical transmittance of a water sample doped with ferrofluid in a weak magnetic field. We investigate also the magneto-optical relaxation when the magnetic field is turned on and when it is turned off, considering several different concentrations of water and glycerin doped with different concentrations of ferrofluid. The mathematical procedures used to analyze our experimental data is also presented.